Attitudes Towards Knowledge Management of School Administrators and Teachers Working in Turkish Schools - DOĞAN, SONER; yiğit, yakup (Alberta Journal of Educational Research, 2015)
The aim of this study is to investigate attitudes of school administrators and teachers working in Turkish schools towards knowledge management. In this research, an explanatory design incorporating quantitative and qualitative methods was used. The quantitative strand of the study was designed as a survey model, and the data was collected from 336 school administrators and teachers who work in the province of Sivas by using the Attitude Scale Towards Knowledge Management (Demir, 2005). The qualitative part of the study was carried out using a case study design, and the researchers used semi-structured interviews to collect data from 12 school administrators and teachers who work in the province of Sivas. To interpret the interview data, descriptive analysis, content analysis, and constant comparison techniques were used. The quantitative findings revealed that school administrators and teachers reported positive attitudes towards knowledge management with respect to self-development and negative attitudes towards communication and commitment. and negative attitudes towards communication and commitment. According to the qualitative findings obtained from questions asked to the participants with respect to communication, commitment, and self-development, participants stated that the knowledge management activities that took place at school were insufficient. Consequently, a knowledge management model suitable for Turkish school context is suggested. L’objectif de cette recherche est d’étudier les attitudes face à la gestion de connaissances qu’ont les administrateurs scolaires et les enseignants dans des écoles turques. Ce projet a employé une conception explicative qui intègre des méthodes quantitatives et qualitatives. La composante quantitative de l’étude a été conçue comme enquête reposant sur l’échelle mesurant l’attitude envers la gestion des connaissances (Demir, 2005) et administrée auprès de 336 administrateurs scolaires et enseignants de la province de Sivas. La composante qualitative de l’étude était basée sur un modèle d’étude de cas dans laquelle les chercheurs ont employé des entrevues semi-structurées pour recueillir des données auprès de 12 administrateurs scolaires et enseignants de la province de Sivas. Des analyses descriptives, des analyses du contenu et des techniques de comparaison constante ont servi dans l’interprétation des données d’entrevue. Les résultats quantitatifs ont révélé que les administrateurs scolaires et les enseignants avaient des attitudes positives face à la gestion des connaissances relativement au développement personnel et des attitudes négatives par rapport à la communication et l’engagement. Les résultats qualitatifs provenant des questions portant sur la communication, l’engagement et le développement personnel indiquent que les participants trouvaient que les activités de gestion des connaissances à l’école étaient insuffisantes. Nous proposons donc un modèle de gestion des connaissances qui convient mieux au contexte des écoles turques.